Foundational Security Principles for Medical Application Platforms* (Extended Abstract) - Vasserman, Eugene Y.; Hatcliff, John (My University, 2015)
We describe a preliminary set of security requirements for safe and secure next-generation medical systems, consisting of dynamically composable units, tied together through a real-time safety-critical middleware. We note that this requirement set is not the same for individual (stand-alone) devices or for electronic health record systems, and we must take care to define system-level requirements rather than security goals for components. The requirements themselves build on each other such that it is difficult or impossible to eliminate any one of the requirements and still achieve high-level security goals.